2016
DOI: 10.1038/srep18846
|View full text |Cite
|
Sign up to set email alerts
|

PYCR1 and PYCR2 Interact and Collaborate with RRM2B to Protect Cells from Overt Oxidative Stress

Abstract: Ribonucleotide reductase small subunit B (RRM2B) is a stress response protein that protects normal human fibroblasts from oxidative stress. However, the underlying mechanism that governs this function is not entirely understood. To identify factors that interact with RRM2B and mediate anti-oxidation function, large-scale purification of human Flag-tagged RRM2B complexes was performed. Pyrroline-5-carboxylate reductase 1 and 2 (PYCR1, PYCR2) were identified by mass spectrometry analysis as components of RRM2B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 43 publications
(84 reference statements)
3
66
0
Order By: Relevance
“…28 PYCR isozymes have also been demonstrated to co-localize with the stress response protein, ribonucleotide reductase small subunit B (RRM2B) to prevent cellular injury from oxidative stress. 29 Recently, a role for PYCR2 in cellular apoptosis was suggested in melanoma cells, as PYCR2 knockdown led to decreased proliferative capacity and activation of AMPK/mTOR-induced autophagy. 19 PYCR2 deficiency led to increased apoptosis under oxidative stress when cells with homozygous frameshift mutations were treated with H 2 O 2 , and knockdown of PYCR2 ortholog, pycr1b, in a zebrafish model resulted in smaller head/brain, shorter body, down-tilted tail, and hypomotility.…”
Section: Discussionmentioning
confidence: 99%
“…28 PYCR isozymes have also been demonstrated to co-localize with the stress response protein, ribonucleotide reductase small subunit B (RRM2B) to prevent cellular injury from oxidative stress. 29 Recently, a role for PYCR2 in cellular apoptosis was suggested in melanoma cells, as PYCR2 knockdown led to decreased proliferative capacity and activation of AMPK/mTOR-induced autophagy. 19 PYCR2 deficiency led to increased apoptosis under oxidative stress when cells with homozygous frameshift mutations were treated with H 2 O 2 , and knockdown of PYCR2 ortholog, pycr1b, in a zebrafish model resulted in smaller head/brain, shorter body, down-tilted tail, and hypomotility.…”
Section: Discussionmentioning
confidence: 99%
“…Zaki et al (2016) found evidence that PYCR2 is involved in regulating apoptosis under conditions of oxidative stress, and the protein likely plays a role in maintaining mitochondrial membrane potential. While mitochondrial dysfunction for PYCR1 had been demonstrated by Reversade et al (2009), a combined role for PYCR1 and PYCR2 in protection against oxidative stress was confirmed by Kuo et al (2016). This explains why mitochondrial dysfunction and increased lactate on brain MRS can be observed in PYCR2 deficiency (personal observations).…”
Section: Diagnosismentioning
confidence: 99%
“…Atf5, mitochondrial Slc25a47, Pycr1[Fiorese et al, 2016;Kuo et al, 2016;Tan, Ooi, Aw, & Hui, 2004]) and there was an increased activation of genes involved in metabolism of extracellular antioxidants (vitamins B5, A and C) in voles from the CEZ. In the spleen, Hp for haptoglobin, an antioxidant that enhances cells' tolerance to F I G U R E 2 Overview of affected liver metabolic pathways between uncontaminated control and CEZ populations of bank voles.…”
mentioning
confidence: 99%